System Leakage in Domestic Solid Waste Management and Community-Based Pathways for Closing the Loop: A Mixed-Methods Evaluation in Tegal Regency, Indonesia - Nur Rochman; Maryono Maryono; Budi Warsito (Lembaga Teewan Journal Solutions, 2026)
Regency-scale domestic waste management in rapidly urbanising regions frequently experiences system leakage, where waste fails to enter or complete controlled management pathways. This study evaluated domestic solid waste management in Tegal Regency, Central Java, Indonesia, using an evaluative-descriptive mixed-methods approach. The analysis integrated waste-balance estimation, policy review, village-level surveys, observations of 14 TPS3R facilities, and community-perception data. The findings reveal substantial leakage within the waste management system. Based on an indicative generation of approximately 670 tons/day, 229.56 tons/day were transported to the Penujah landfill, while 53.21 tons/day were processed through recycling industries. These figures indicate an estimated leakage of 57.8%, increasing to 62.0% under the local planning baseline. Organic waste, particularly food and kitchen waste, constituted the largest fraction (49.87%), highlighting the importance of source separation, composting, and community-based organics management. TPS3R performance remained limited: among the 14 observed facilities, 64.3% were inactive, 14.3% partially active, and only 21.4% fully operational. Major implementation gaps involved weak integration among waste separation, collection, treatment, transport, recycling markets, financing, and monitoring systems. The study proposes a community-integrated management model supported by digital mass-balance monitoring to reduce leakage and strengthen decentralised waste management in developing-country contexts.